Desmoplakin and periplakin genetically and functionally contribute to eosinophilic esophagitis - Tetsuo Shoda (Nature Portfolio, 2021)
Eosinophilic esophagitis (EoE) is a chronic allergic inflammatory disease with a complex underlying genetic etiology. Here, the authors identify a series of rare variants in DSP and PPL in multiplex families with EoE and uncover a pathogenic role for desmosomal dysfunction in EoE.